Microbial transformation of the diterpene mulin-11,13-dien-20-oic acid by Mucor plumbeus - Areche, C.; Loyola, L.A.; Borquez, J.; Rovirosa, J.; San-Martin, A.
Twonewmulinane-type derivatives: 16-hydroxymulin-11,13-dien-20-oic (2)acid and 7á,16-dihydroxymulin-11,13-dien-20-oic (3)acid were obtained by microbial transformation of mulin-11,13-dien-20-oic acid (1), along with tyrosol (4)using liquid cultures of Mucor plumbeus. The latter compound has not been previously identified in the genus Mucor. Structural elucidation of thesemetabolites was achieved using 1D- and 2D-NMR spectroscopy
Keywords: NMR; 1HNMR; 13C NMR; 2D NMR; AZORELLA COMPACTA; BIOTRANSFORMATION; DITERPENOIDS; MUCOR PLUMBEUS; TYROSOL